2019
DOI: 10.1530/joe-18-0520
|View full text |Cite
|
Sign up to set email alerts
|

Metformin improves ovarian insulin signaling alterations caused by fetal programming

Abstract: Insulin resistance is the decreased ability of insulin to mediate metabolic actions. In the ovary, insulin controls ovulation and oocyte quality. Alterations in ovarian insulin signaling pathway could compromise ovarian physiology. Here, we aimed to investigate the effects of fetal programming on ovarian insulin signaling and evaluate the effect of metformin treatment. Pregnant rats were hyperandrogenized with testosterone and female offspring born to those dams were employed; at adulthood, prenatally hyperand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
7
14
0
Order By: Relevance
“…Similar to our previous findings (Abruzzese et al 2019b), lipid profile was altered at adulthood in PH animals, which showed increased levels of LDL-cholesterol (p<0.01) and TG (p<0.01) as compared with the control group. Regarding hormonal steroid profile, as previously found (Heber et al 2019), prenatal androgenization led to an increase in testosterone levels in the PHanov group (p<0.01) and a decrease in estradiol levels in both PHiov and PHanov groups (p<0.05), without alterations in progesterone levels (p>0.05). Moreover, neither of the PH…”
Section: Hormonal and Metabolic Determinationssupporting
confidence: 76%
See 2 more Smart Citations
“…Similar to our previous findings (Abruzzese et al 2019b), lipid profile was altered at adulthood in PH animals, which showed increased levels of LDL-cholesterol (p<0.01) and TG (p<0.01) as compared with the control group. Regarding hormonal steroid profile, as previously found (Heber et al 2019), prenatal androgenization led to an increase in testosterone levels in the PHanov group (p<0.01) and a decrease in estradiol levels in both PHiov and PHanov groups (p<0.05), without alterations in progesterone levels (p>0.05). Moreover, neither of the PH…”
Section: Hormonal and Metabolic Determinationssupporting
confidence: 76%
“…Prenatal exposure to a suboptimal intrauterine environment could lead to long term effects affecting reproductive functions. To study the impact of fetal programming of animals exposed to androgens, we reproduced a rodent model of prenatal androgen excess widely used (Wolf 2002;Ramezani Tehrani et al 2014;Abruzzese et al 2016Abruzzese et al , 2019aHeber et al 2019). Here, using this model, we addressed the question of whether ovarian lipid metabolism and specifically cholesterol metabolism are impaired in these animals when adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum testosterone levels, determined by radioimmunoassay (RIA) (Amalfi et al, 2012), were increased in both PH phenotypes, being higher in the PHanov group than in the PHiov and control groups (control= 67.76 ± 13.52;PHiov= 115.84 ± 34.82;PHanov= 154.34 ± 32.00;control + Metformin= 101.27 ± 17.35;PHiov= 123.73 ± 35.90;PHanov= 129.34 ± 10.65). As it has been previously reported (Heber et al, 2019), metformin treatment did not modify the testosterone levels of the PHiov or PHanov groups, but tended to diminish those of the PHanov group.…”
Section: Animals and Experimental Designsupporting
confidence: 75%
“…This phenomenon of the same environmental stressor leading to different phenotypes was observed in a rat model of in utero androgen excess, where female offspring presented two distinctive phenotypes, both with alterations in reproductive and metabolic function. However, one phenotype presented more severe alterations and was less receptive to pharmacological treatment [ 112 , 113 ]. Until recently, the long-term outcomes of developmental programming were considered to be irreversible; however, there is evidence of the reversibility of the postnatal programmed phenotype.…”
Section: Phenotypical Plasticitymentioning
confidence: 99%